KEPATUHAN WAJIB PAJAK BUMI BANGUNAN: PENDAPATAN MASYARAKAT, TINGKAT PENDIDIKAN DAN SOSIALIASI PERPAJAKAN DI KOTA BINJAI - Zulferry, Diva Mumtazah Putri; Nasution, Yenni Samri Juliati; Syafina, Laylan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
One of the ways the government earns money is through taxes to fund social programs, public services, and infrastructure development. This study determines how taxpayer compliance in paying Land and Building Tax (PBB) in Damai Sub-district, Binjai City is influenced by community income, education level, and tax socialization. The efficiency of the local tax system in generating revenue for city development depends on tax compliance. For this study, primary data were collected from land and building taxpayers through the distribution of questionnaires. The sample size of this study was 94 people, who were selected using a purposive sampling technique. Multiple linear regression, classical assumption testing, data quality assessment, descriptive statistics, and hypothesis testing were used to test the data and analyzed with SPSS version 23. The research findings show that community income, education level, and tax socialization affect taxpayer compliance in paying land and building taxes.